2016
DOI: 10.4172/2471-9552.1000115
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease of the Immune System: A New Variant of Immune Deficiency

Abstract: The interaction between infectious pathogens and the immune system has been a focus of research for many years. However, the failure of re-recognition or immune memory of infectious pathogen remains a clear mystery A memory B cell defect coupled with low levels of C1-INH and/or C1-INH function-failure of both the innate and adaptive immune components-may lead to persistent unresolved infection. Here we present 3 case studies that explore the abnormal immune response that may lead to persistent infection. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, this is unsurprising because the inability to mount an appropriate immune response to eliminate cell debris, could lead to damage pile-up and thus trigger chronic inflammation. Indeed, an overlap between primary immunodeficiencies and inflammatory diseases has been reported for various inflammatory diseases such as inflammatory bowel disease, rheumatoid arthritis and others ( Fodil et al , 2016 ; Melamed, 2016 ). Perhaps the best example is chronic inflammation in Crohn’s disease, which was initially regarded as an autoimmune disease, but is now thought to be an aftermath of defective production of immune factors, diminished immune cell recruitment and/or failed autophagy ( Marks and Segal, 2008 ; Marks et al , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is unsurprising because the inability to mount an appropriate immune response to eliminate cell debris, could lead to damage pile-up and thus trigger chronic inflammation. Indeed, an overlap between primary immunodeficiencies and inflammatory diseases has been reported for various inflammatory diseases such as inflammatory bowel disease, rheumatoid arthritis and others ( Fodil et al , 2016 ; Melamed, 2016 ). Perhaps the best example is chronic inflammation in Crohn’s disease, which was initially regarded as an autoimmune disease, but is now thought to be an aftermath of defective production of immune factors, diminished immune cell recruitment and/or failed autophagy ( Marks and Segal, 2008 ; Marks et al , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested a hypothesis in which the combination of an epigenetic factor such as an infectious pathogen with a low level of memory B cells may contribute to abnormal signaling, which may lead to a neuroinflammatory response [Melamed, ]. Based on this hypothesis, the decreased TLR‐4 signaling observed with IVIG treatment in this study may suggest that IVIG was able to downregulate the proinflammatory response seen in these patients.…”
Section: Discussionmentioning
confidence: 53%
“…There was an apparent downregulation of C1-INH levels after IVIG therapy and an associated increase in the incidence of IVIG-related AEs, suggesting a possible relationship ( 8 ). Additionally, further findings suggest low level and function of C1-INH may play a role in the relationship between a post-infectious response and neurologic changes, a form of post-infectious autoimmunity that results in various neurologic symptoms ( 9 ).…”
Section: Introductionmentioning
confidence: 99%